Clear phylogeographical structures shed light on the origin and dispersal of the aquatic boreal plant Hippuris vulgaris - Yu, Yinjiao; Lu, Qixiang; Lapirov, Alexander G.; Freeland, Joanna; Xu, Xinwei (Frontiers in Plant Science, 2022)
Aquatic plants are an important ecological group in the arctic flora; however, their evolutionary histories remain largely unknown. In order to deepen our understanding of the evolution of these plants, we explored the phylogeographical structure of an aquatic boreal plant Hippuris vulgaris in a broad geographical sampling from Eurasia and North America using the chloroplast intergenic spacer psbA-trnH and seven nuclear microsatellite loci. Two closely-related species H. lanceolata and H. tetraphylla were also included because of their taxonomic controversy. Both chloroplast DNA sequences and nuclear microsatellite data revealed three genetic lineages with distinct distribution ranges. Incongruence between nuclear and chloroplast DNA lineages occurred in 14 samples from Russian Far East and Europe caused by inter-lineage hybridization. No private haplotypes or independent genetic clusters were evident in H. lanceolata or H. tetraphylla, suggesting that these two species should be considered conspecific ecotypes of H. vulgaris. Analysis using Approximate Bayesian Computation-Random Forest approach suggests that Hippuris vulgaris originated in China, followed by dispersal into Russia plus Northeast China, then successively westwards into Europe and North America, and finally into the Russian Far East from both North America and Russia plus Northeast China. This study is the first to elucidate the historical dispersal processes of a circumarctic aquatic plant across the entirety of its range.